LIDAR simulation and digital model processing - Zhou, Kai Jing. (2010)
Digital surface model (DSM) is topographic maps of the earth's surface which includes buildings, vegetation, roads, as well as natural terrain features. On the other hand, digital terrain model (DTM) is a so-called bare-earth model and devoid of landscape features. LIDAR (Light Detection and Ranging), being one of the latest optical remote sensing technologies has gained increasing acceptance for topographic mapping due to its high degree of precision and minimum human dependence. The objective of this project is to reconstruct the 3D object models from Light Detection and Ranging (LIDAR) data by performing grid interpolation on these objects and also extract objects or bare earth based on users’ interests. The general project procedure can be summarized as 1) Prepare LIDAR data for visualization; 2) Investigate various interpolation methods for both speed and accuracy matters; 3) Prepared gridded surface for visualization or further filtering process; 4) Data filtering and visualization based on individual interests. The main contributions to achieve these processes are the algorithms for LIDAR simulation and the software used to achieve these operations is MATLAB R2009a.